Exosome dynamics and changes in a selection of their microRNA cargo in response to an acute bout of eccentrically-biased exercise in healthy human volunteers - Lovett, Jason (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.